STUDY ON PLACEMENT AND MASS RATIO OF MULTIPLE TUNED MASS DAMPERS - Bukit (NIM 25004046), Bahter
ABSTRACT: The objective of this research is to study the structure by placing MTMD to receive earthquake load and analyze the most effective proportion of mass ratio for each MTMD location. This dynamic analysis used a 6 story structure linear elastic as the main structure. Structure is modeled as two. The main external force is ground acceleration due to earthquake, which was given in the form of time history. Maximum displacement ratio and drift shows the effectiveness of TMD and MTMD. Numerical anaysis was conducted in six damper placement conditions. First condition was TMD on 6th floor, second was MTMD on 6th, third was MTMD on 6th and 4th, fourth was MTMD on 6th and 2nd, fifth was MTMD on 4th and 2nd, and the last condition was MTMD placement on 6th, 4th, and 2nd. A six story structure without TMD was used as a comparison. Based on structure maximum displacement ratio and maximum drift, the most effective MTMD placement condition was on the 6th floor. As TMD mass ratio and total MTMD mass ratio increases, the effectiveness of TMD and MTMD system also increased. Numerical analysis shows TMD and MTMD placement on structure reduces the maximum drift, but maximum deviation location was the same.